IMPLEMENTASI METODE MUROJA’AH DALAM MENINGKATKAN KUALITAS HAFALAN AL-QUR’AN SANTRI DI PESANTREN AL-QUR’AN ALMUBARAK - Resi Nurul Istiqamah; Martin Kustati; Gusmirawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Qur'an is a holy book revealed to the Prophet Muhammad SAW. In addition to being a guide, the Qur'an can also be memorized in detail by humans, both in terms of letters, words, and punctuation. The Qur'an is a book whose language is preserved and guaranteed by Allah SWT. This study aims to analyze the implementation of the muroja'ah method in improving the quality of Qur'an memorization among students at Islamic boarding schools. This study uses a qualitative approach with a descriptive method, where data is collected through observation, in-depth interviews, and documentation of muroja'ah activities. The results of the study indicate that the implementation of the muroja'ah method is carried out through several systematic stages, namely daily muroja'ah, monthly muroja'ah, and monthly muroja'ah with memorization targets adjusted to the abilities of the students. The findings indicate that the muroja'ah method has a significant impact on improving the quality of students' memorization, as seen in terms of the strength of memorization, accuracy of recitation (tajwid), and fluency in repeating memorization. Factors supporting the success of this method include student discipline, instructor competence, a structured schedule, and a conducive boarding school environment. Meanwhile, the inhibiting factors found include time constraints and varying levels of concentration among students. This study concludes that the muroja'ah method is an effective strategy in maintaining and improving the quality of Al-Qur'an memorization.